Hepatocholedocho lithiasis.: Statistical studies - Valls, Alberto (Cirugía del Uruguay, 1989)
Authors point out several facts of great importance to surgeons: 1. The growing frequence of main biliary duct lithlasis, which rises to 73% in over-70 year old patients